TUTURAN PENDERITA AFASIA BROCA PASCA STROKE - SURYANI, YUNITA (Sasando, 2019)
Speech sufferers of post-stroke of broca’s aphasia is the language ability of brain injury sufferers. Brain injury or aphasia in stroke sufferers can be in the form of blocked arteries or ischemic and ruptured blood vessels or called hemorrhagic. In this study, focused on hemorrhagic type post-stroke aphasia sufferers. Post-stroke sufferers experience changes in behavior, one of the changes is a change in language or in this study stated by speech when communicating. The field of study of this research is pragmatics, namely pragmatically describing speech of aphasia sufferers after stroke which includes the ability to state the truth (representative), the ability to rule (directive), the ability to say thank you, praise, complain, blame, and congratulate (expressive), the ability to carry out commands (commissive), and the ability to decide, cancel, prohibit, permit, grant, request an explanation (declarative).